2017
DOI: 10.1108/ijccsm-01-2017-0009
|View full text |Cite
|
Sign up to set email alerts
|

Key sectors in carbon footprint responsibility at the city level: a case study of Beijing

Abstract: Purpose This paper aims to identify key sectors in carbon footprint responsibility, an introduced concept depicting CO2 responsibilities allocated through the supply chain containing sectoral activities and interactions. In detail, various key sectors could be identified according to comparative advantages in trade, sectoral linkage and sectoral synergy within the supply chain. Design/methodology/approach A semi-closed input–output model is used to make the household income–expenditure relationship endogenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
(88 reference statements)
0
3
0
1
Order By: Relevance
“…Quantifying household indirect and direct energy consumption-demand relationships using IOA is a particularly widely studied topic (Supasa et al, 2017;Singh et al, 2018;Long et al, 2019). In addition, input-output models have established an important role in measuring household carbon emissions, especially in China (Xu L et al, 2021;Tian et al, 2017;Zhang and Lei, 2017). Many studies have confirmed the contribution of IOA models in promoting energy efficiency and in developing energy efficiency policies of household (Stagnitta et al, 2020).…”
Section: Input-output Approachmentioning
confidence: 99%
“…Quantifying household indirect and direct energy consumption-demand relationships using IOA is a particularly widely studied topic (Supasa et al, 2017;Singh et al, 2018;Long et al, 2019). In addition, input-output models have established an important role in measuring household carbon emissions, especially in China (Xu L et al, 2021;Tian et al, 2017;Zhang and Lei, 2017). Many studies have confirmed the contribution of IOA models in promoting energy efficiency and in developing energy efficiency policies of household (Stagnitta et al, 2020).…”
Section: Input-output Approachmentioning
confidence: 99%
“…Both original and Cella HEM have been used in literature to study industrial-economic linkages (Song et al , 2006; Cai and Leung, 2004). HEM has also been applied to various dimensions and aspects related to environmental problems these include: water problem (Duarte et al , 2002; Blanco and Thaler, 2014; Deng et al , 2018); regional (Ali, 2015; Zhao et al , 2015; Wang et al , 2013) and inter-regional (Zhao et al , 2016) sectoral carbon linkages; energy linkages (Guerra and Sancho, 2010); household carbon linkages at country (Zhang et al , 2017a; Perobelli et al , 2015; Zhang et al , 2017b) and city (Tian et al , 2017; Liao et al , 2017) levels; and air pollutants at regional (He et al , 2017) and inter-regional levels (Wang et al , 2017a). …”
Section: Literature Reviewmentioning
confidence: 99%
“…household carbon linkages at country (Zhang et al , 2017a; Perobelli et al , 2015; Zhang et al , 2017b) and city (Tian et al , 2017; Liao et al , 2017) levels; and…”
Section: Literature Reviewmentioning
confidence: 99%
“…Entre sus principales resultados destacan que, en términos absolutos, las economías más grandes, como Alemania, presentaron vínculos de dependencia 7 Aplicaciones recientes del MEH para identificar la importancia de un sector en la estructura productiva de un país se encuentran en Kay (2017), Cassar (2017), Song et al (2005). Esta metodología también se ha utilizado recientemente para identificar los sectores clave responsables de la huella de carbono (Tian et al, 2018) y (Zhang et al, 2018), y para medir eficiencia energética (Guerra y Sancho, 2010). más fuertes.…”
Section: Revisión De La Literaturaunclassified